ANALISIS ATAS PENAFSIRAN FAKHR AL-DIN AL-RAZI TENTANG AL-HURUF AL-MUQATTA’AH - Ilham Ilyas Ilyas (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2019)
This article discusses about al-huruf al-muqatta’ah in the book Mafatih al-Gaib by Fakhr al-Din al-Razi. Which contains discussion, the first discussion: how is Fakhr al-Din al-Razi’s interpretation about al-huruf al-muqatta’ah ? the second discussion: what is Fakhr al-Din al-Razi’s comment on the interpretation of scholars about al-huruf al-muqatta’ah ? this research is a qualitative tafsir study based on the study of the kitab. The propose of the study is that the data is taken from the kitab related to the research title. The approach used is tafsir science approach, language and philosophy. Researchers make al-huruf al-muqatta’ah as an object of research by using several books related to it to find out the interpretation of scholars (especially Fakhr al-Din al-Razi) about al-huruf al-muqatta’ah. The reason why the researcher choose this title its because there are differences in opinions of scholars into two opinions. First opinion: these letters are the secret of Allah, second opinion: the purpose of al-huruf al-muqatta’ah can be known and there are many words of scholars about itu, even though there was no direct axplanation from the Prophet Muhammad about the meaning of al-huruf al-muqatta’ah. Therefore researchers think it is necessary to conduct research. The result of this study founds that Fakhr al-Din al-Razi strengthened the opinion that al-huruf al-muqatta’ah is the name of surah and to attract the attention of non muslims to read the Qur’an after they advised one another to turn away from the Qur’an.